The Role of Sectoral Growth Patterns in Labor Market Development - Arias-Vazquez, Francisco Javier; Lee, Jean N.; Newhouse, David (World Bank, Washington, DC, 2013)
This paper investigates the relationship between sectoral growth patterns and employment outcomes both across and within countries. Consistent with the literature on sectoral growth patterns and poverty alleviation, a broad cross-country analysis reveals that in middle-income countries, employment responds more to growth in less productive and more labor-intensive sectors. Employment in middle-income countries is susceptible to a resource curse, and grows rapidly in response to manufacturing and export manufacturing growth. Sectoral growth patterns have surprisingly few discernible effects on the prevalence of wage or agricultural employment. In country case studies of Brazil, Indonesia, and Mexico, the effects of different sectoral growth patterns are context dependent. Within these countries, differences in sectoral growth effects on employment and wages are substantially reduced in states or provinces with higher measured labor mobility. Consistent with this, aggregate employment and wage effects of growth by sector are close to uniform when examined over longer time horizons, after labor has an opportunity to adjust across sectors. The results reinforce the importance of growth in more labor-intensive sectors and manufacturing in generating employment in middle-income countries, although only manufacturing and natural resource growth show distinctive labor market effects, and those are largely limited to employment and unemployment. Finally, job mobility may be an important mechanism to diffuse the benefits of capital-intensive growth.